Synthesis, curing kinetics, mechanical and thermal properties of novel cardanol-based curing agents with thiourea. Issue 107 (7th November 2016) - Ma, Zhe; Liao, Bing; Wang, Kun; Dai, Yongqiang; Huang, Jianheng; Pang, Hao
Abstract : A new flexible cardanol-based epoxy curing agent with cross-linkable thiourea groups was synthesized from cashew nut shell. Abstract : Two new flexible cardanol-based epoxy curing agents with cross-linkable thiourea groups ([2-(2-amino-ethylamino)-ethyl]-thiourea of modified cardanol and [2-(2-amino-ethylamino)-ethyl]-thiourea of modified cardanol 2, 3-dihydroxy propyl ether, ETC and TCP for short, respectively) were synthesized using a Mannich reaction. The structure of the prepared curing agents was analyzed by a nuclear magnetic resonance (NMR) and Fourier transform infrared spectroscopy (FT-IR). The curing kinetics of ETC (or TCP) cured diglycidyl ether of biphenyl A (DGEBA) epoxy resins was investigated using the Kissinger, Flynn–Wall–Ozawa and Crane methods by non-isothermal differential scanning calorimetry (DSC). Thermal properties of the cured epoxy resins were evaluated with thermogravimetric analysis (TGA) and DSC. The morphology and mechanical properties of the cured epoxy resins were also studied. The results showed that the epoxy curing agents had a high-reactivity and a low-viscosity, especially at low temperatures. The activation energy of ETC/DGEBA and TCP/DGEBA calculated by the Kissinger method were 53.6 and 60.5 kJ mol −1, respectively. The toughness of the cured epoxy resin was noticeably improved by the introduction of two new flexible curing agents. The glass transition temperature ( T g ) decreased with the introduction of cardanol-based curing agents in an epoxy resin system. In addition, the cured epoxy materials exhibited good mechanical properties.